The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0100-39842007000300006
|View full text |Cite
|
Sign up to set email alerts
|

Obstrução intestinal pós-gastroplastia redutora pela técnica de higa para tratamento da obesidade mórbida: aspectos por imagem

Abstract: OBJETIVO: O objetivo deste estudo foi descrever os principais aspectos radiológicos encontrados nas obstruções intestinais pós-operatórias em pacientes submetidos a derivação gastrintestinal em Y de Roux pela técnica de Higa. MATERIAIS E MÉTODOS: Foram estudados 10 pacientes com obstrução intestinal no pós-operatório de gastroplastia redutora, examinados entre novembro de 2001 e abril de 2006. Os casos foram obtidos em sete instituições hospitalares distintas. RESULTADOS: Nos 10 pacientes, a obstrução ocorreu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…In this prospective study, we investigated the value of contrast-enhanced MDCT in identifying postoperative complications of laparoscopic Roux-en-Y gastric bypass and laparoscopic sleeve gastrectomy in symptomatic patients. According to multiple previous studies contrastenhanced CT imaging is considered the method of choice for investigation of abdominal symptoms, especially of patients undergoing gastric bypass [36][37][38]. Merckle et al [39] reported that CT can provide a detailed view of the anatomy after Roux-en-Y gastric bypass.…”
Section: Discussionmentioning
confidence: 99%
“…In this prospective study, we investigated the value of contrast-enhanced MDCT in identifying postoperative complications of laparoscopic Roux-en-Y gastric bypass and laparoscopic sleeve gastrectomy in symptomatic patients. According to multiple previous studies contrastenhanced CT imaging is considered the method of choice for investigation of abdominal symptoms, especially of patients undergoing gastric bypass [36][37][38]. Merckle et al [39] reported that CT can provide a detailed view of the anatomy after Roux-en-Y gastric bypass.…”
Section: Discussionmentioning
confidence: 99%
“…18 Pacientes com sintomas abdominais inespecíficos e vagos devem ser prontamente submetidos à tomografia com contraste que, além de diagnosticar a obstrução, permite avançar na etiologia diagnóstica, sendo indicativa de hérnias. 19 Embora esse estudo não trate especificamente de pacientes de cirurgia bariátrica, existe coincidência entre as causas aqui encontradas e aquelas presentes em pacientes que se submetem à cirurgia, segundo a literatura. 18 Entre os homens, nota-se um aumento da gama de causas de morte, o que é esperado em um contexto de transição epidemiológica.…”
Section: Discussionunclassified
“…Adhesions were found in 0.42% of the patients in this research. In a study performed with a sample of 10 acute abdomen patients, three of them had adhesions as the cause, showing that it is an important cause of bowel obstruction 13 .…”
Section: Discussionmentioning
confidence: 99%